Self-assembled multiferroic epitaxial BiFeO3-CoFe2O4 nanocomposite thin films grown by RF magnetron sputtering - Kim, Tae Cheol; Ojha, Shuchi; Tian, Guo; Lee, Seung Han; Jung, Hyun Kyu; Choi, Jun Woo; Kornblum, Lior; Walker, Frederick J.; Ahn, Charles H.; Ross, Caroline A.; Kim, Dong Hun (ROYAL SOC CHEMISTRY, 2018)
Self-assembled nanocomposites consisting of ferrimagnetic CoFe2O4 and ferroelectric BiFeO3 were grown on Nb-doped SrTiO3 (001) or SrTiO3-buffered Si (001) substrates using radio frequency magnetron sputtering. Spinel CoFe2O4 formed as epitaxial pillars within a perovskite BiFeO3 matrix, similar to nanocomposites grown by pulsed laser deposition. CoFe2O4 and BiFeO3 grew with a cube-on-cube epitaxy on Nb-doped SrTiO3, with partial relaxation of the in-plane strain of BiFeO3. The sputter-grown nanocomposites showed an out-of-plane magnetic easy axis as a result of both the shape anisotropy of the pillars and the magnetoelastic anisotropy of CoFe2O4, but the latter was dominant. The BiFeO3 matrix exhibited ferroelectric domains, and the removal of BiFeO3 led to the reduction of magnetic anisotropy by the strain relaxation of CoFe2O4. For potential application in devices, the nanocomposites were integrated on buffered silicon substrates. Templating of the CoFe2O4 nanopillars was achieved by substrate patterning. These techniques facilitate the incorporation of multiferroic nanocomposites into memory and other devices.
Keywords: FUNCTIONALITY; DEPOSITION; ANISOTROPY